EgmiR5179 Regulates Lipid Metabolism by Targeting EgMADS16 in the Mesocarp of Oil Palm (Elaeis guineensis) - Wang, Yifei; Zou, Jixin; Zhao, Jin; Zheng, Yusheng; Li, Dongdong (Frontiers in Plant Science, 2021)
EgMADS16, one of the MADS-box transcription factors in oil palm, has a high expression level in the late fruit development of the oil palm fruit mesocarp. At the same time, it is also predicted to be the target gene of EgmiR5179, which has been identified in previous research. In this paper, we focused on the function and regulatory mechanism of the EgMADS16 gene in oil palm lipid metabolism. The results indicated that the transcription level of EgMADS16 was highest in the fourth stage, and a dual-luciferase reporter assay proved that the EgMADS16 expression level was downregulated by EgmiR5179. In both the OXEgMADS16 Arabidopsis seeds and oil palm embryonic calli, the total lipid contents were significantly decreased, but the contents of C18:0 and C18:3 in OXEgMADS16 lines were significantly increased. As expected, EgmiR5179 weakened the inhibitory effect of EgMADS16 on the oil contents in transgenic Arabidopsis plants that coexpressed EgmiR5179 and EgMADS16 (OXEgmiR5179-EgMADS16). Moreover, yeast two-hybrid and BiFC analyses suggested that there was an interaction between the EgMADS16 protein and EgGLO1 protein, which had been proven to be capable of regulating fatty acid synthesis in our previous research work. In summary, a model of the molecular mechanism by which miRNA5179 targets EgMADS16 to regulate oil biosynthesis was hypothesized, and the research results provide new insight into lipid accumulation and molecular regulation in oil palm.